2021
DOI: 10.1093/nar/gkaa1277
|View full text |Cite
|
Sign up to set email alerts
|

Another layer of complexity inStaphylococcus aureusmethionine biosynthesis control: unusual RNase III-driven T-box riboswitch cleavage determinesmetoperon mRNA stability and decay

Abstract: In Staphylococcus aureus, de novo methionine biosynthesis is regulated by a unique hierarchical pathway involving stringent-response controlled CodY repression in combination with a T-box riboswitch and RNA decay. The T-box riboswitch residing in the 5′ untranslated region (met leader RNA) of the S. aureus metICFE-mdh operon controls downstream gene transcription upon interaction with uncharged methionyl-tRNA. met leader and metICFE-mdh (m)RNAs undergo RNase-mediated degradation in a process whose molecular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Hence, RNases J1/J2 are not only essential for stress responses by controlling mRNA degradation but they also contribute to generate sRNA from mRNAs. Very recently, a rather similar degradation mechanism was described in the maturation of the T-box riboswitch in the 5′UTR of the metlCFE-mdh operon (Wencker et al, 2021). Indeed, in the absence of methionine and after cleavage of the met leader by RNase III, the RNases J1/J2 mediate degradation of the mRNA from the 5′-end generating more stable transcripts toward the 3′-end.…”
Section: The Dual Ribonuclease J1/j2 Generates the 3′utr-derived Rsag Srnamentioning
confidence: 65%
“…Hence, RNases J1/J2 are not only essential for stress responses by controlling mRNA degradation but they also contribute to generate sRNA from mRNAs. Very recently, a rather similar degradation mechanism was described in the maturation of the T-box riboswitch in the 5′UTR of the metlCFE-mdh operon (Wencker et al, 2021). Indeed, in the absence of methionine and after cleavage of the met leader by RNase III, the RNases J1/J2 mediate degradation of the mRNA from the 5′-end generating more stable transcripts toward the 3′-end.…”
Section: The Dual Ribonuclease J1/j2 Generates the 3′utr-derived Rsag Srnamentioning
confidence: 65%
“…For instance, some riboswitches that are widely distributed among different bacterial species (i.e., TPP, FMN riboswitches) could be used as broad-spectrum antibacterial targets, while others that are found specifically in individual genus or species could constitute selective drugs (e.g., targeting preQ-1 or purine-riboswitches) [ 26 ]. Recently, it was reported that T-boxes in Staphylococcus aureus contain species-specific structural features that play a central role in riboswitch structural conformation and function, allowing the adaptation to specific metabolic environments, making them promising, lineage-specific drug targets [ 27 , 28 , 29 , 30 ]. Furthermore, some riboswitches regulate the expression of several genes that are fundamental for bacterial survival.…”
Section: Introductionmentioning
confidence: 99%
“…The trpX T-box comprises 461 nt and is relatively large in size compared to other T-boxes 21 . However, a T-box with a similar size (440 nt) which is involved in methionine biosynthesis has been found in Staphylococcus aureus 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in S. aureus where the deletion of the antiterminator and terminator stretch led to an activated transcription independent of methionine concentration. Therefore, the T-box riboswitch mechanism depends on an effective termination site 63 .…”
Section: Discussionmentioning
confidence: 99%